2015
DOI: 10.1155/2015/730618
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aging Agricultural Labor Population on Farmland Output: From the Perspective of Farmer Preferences

Abstract: Chinese agriculture is facing an aging workforce which could negatively impact the industry. In this context, research is needed on how work preferences and age of farmers affect agricultural output. This paper attempts to investigate these factors to more fully understand the impact of an aging agricultural labor population on agricultural production. The results show that, in this context of aging, changes in the working-age households have a significant impact on agricultural output. Despite the fact that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 14 publications
(13 reference statements)
11
57
0
1
Order By: Relevance
“…This is a potential threat to the development of captured-shrimp value chain in the near future. This findings is similar to Guo, et al (2015) who reported a similar trend in the agricultural labour population in China. The strength and resourcefulness of youths could have enable them achieve more productivity and financial reward in shrimp value chain.…”
Section: Discussionsupporting
confidence: 91%
“…This is a potential threat to the development of captured-shrimp value chain in the near future. This findings is similar to Guo, et al (2015) who reported a similar trend in the agricultural labour population in China. The strength and resourcefulness of youths could have enable them achieve more productivity and financial reward in shrimp value chain.…”
Section: Discussionsupporting
confidence: 91%
“…As farmers' advance in age, they become weak and are no more effective as they were young and hence the negative relationship of farming experience with labour productivity. This agrees with the ndings of Guo et al [26] that an increase in age is not conducive to improving agricultural output. This is at variance with the ndings of Afari [27] that farmers who are more productive may have spent a greater part of their formative years on the farm and have at least learnt a lot of skills (at least in traditional way) in making good use of available inputs at their disposal.…”
Section: Socio-economic Determinants Of Averting Expenditure On Malariasupporting
confidence: 93%
“…As farmers' advance in age, they become weak and are no more effective as they were young and hence the negative relationship of farming experience with labour productivity. This agrees with the findings of [26] that an increased in age is not conducive to improving agricultural output. This is at variance with the findings of [27] that farmers who are more productive may have spent a greater part of their formative years on the farm and have at least learnt a lot of skills (at least in traditional way) in making good use of available inputs at their disposal.…”
Section: Socio-economic Determinants Of Averting Expenditure On Malariasupporting
confidence: 92%